The Influence of Age And Affective Domain in Second/Foreign Language Acquisition - Sultan, Sultan (State University of Makassar, 2022)
This study investigated the relationship between the student profile in studying English as a second/foreign language (ESL/EFL) and Yorio’s taxonomy. The method used in this research was case study. This was done by interviewing one student from a non-English Speaking Background (NESB) who was studying English in Australia. The respondent was a student from Indonesia who was studying at ELICOS program at Victoria University, Melbourne Australia on January 2005. The data from the interview was analysed using Yorio’s taxonomy. The results of the study showed that (1) there was a positive correlation between the student profile in learning English and age and affective domain. (2) Positive attitude and the combination of instrumental and integrative motivation had significant impact on his way in studying English as a second/foreign language.Keywords: Yorio’s taxonomy, age, critical period, affective domain, motivation, egocentric factors.